Osteochondroma of the Temporomandibular Joint Treated by Means of Condylectomy and Immediate Reconstruction with a Total Stock Prosthesis - Miguel-Angel Morey-Mas; Jorge Caubet-Biayna; José-Ignacio Iriarte-Ortabe (eJournal of Oral Maxillofacial Research, 2010)
Background: Osteochondromas are one of the most common benign tumours of bone, but they are rare in the craniofacial region. These condylar tumours have been variably treated, including resection through local excision or condylectomy with or without reconstruction.Methods: A case of osteochondroma of the mandibular condyle and cranial base arising concurrently in the 76 years old patient was presented. The surgical excision of the skull base lesion and condylectomy with immediate reconstruction of temporomandibular joint was applied.Results: Based on the history, clinical examination and radiographic findings, osteochondroma of the skull base was diagnosed, with a concurrent lesion of the condylar process. Treatment methods for this patient included excision of the skull base tumour and condylectomy with immediate temporomandibular joint reconstruction using appropriately sized stock total temporomandibular joint prosthesis. At the 24 month follow-up, patient was free of pain and her maximal incisal opening was maintained, with no radiographic evidence of tumour recurrence or failure of the device.Conclusions: Temporomandibular joint stock total replacement prosthesis became a good option to reconstruct both the fossa and the condyle in a one-stage surgery, due to the fact that both the condylar/mandibular and the fossa implants were stable in situ from the moment of fixation, with a good outcome at 24 month follow-up, with no loosening of the screws nor failure of the device.